Electronic solution with joysticks for laparoscopic equipment - Costa, A. (2022)
laparoscopic instruments. Many attempts of new models for handles of these equipment’s have already been proposed in an effort to combat this ergonomic problem in this type of instrument. The developed work aimed to develop an electronic solution for laparoscopic instruments in order to provide greater comfort to surgeons in the area. As a complement, a handle was manufactured to illustrate the system after downscaling for the surgeon to handle. Also, as a complement, a manual laser measuring plate was developed for future tests with the system attached to the handle. During the elaboration of the work was involved in the process the use of an Arduino Uno board among other electronic components, besides the design of parts in software, the use of 3d printing and laser cutting. The results obtained after the assembly of the electronic mechanism showed that it is possible to obtain the necessary movements for a surgical tool through an electronic drive, avoiding musculoskeletal injuries in surgeons who handle this equipment due to less repetitive efforts during operations.